Genomics of Lynch syndrome and Constitutional mismatch repair deficiency syndrome - Lamola, Lindiwe (Division of Human Genetics, 2018)
Introduction: The mismatch repair system plays an important role in maintaining the genome integrity as it functions to correct mismatches during DNA replication. Heterozygous mutations in one of the mismatch repair (MMR) genes e.g. MLH1, MSH2, MSH6 and PMS2 cause the dominant adult cancer syndrome termed Lynch syndrome (or hereditary non-polyposis colorectal cancer). In our South African cohort, the MLH1 exon 13 c.1528C>T mutation is the most common Lynch syndrome-causing variant in the Mixed Ancestry population. Recently, a patient homozygous for this mutation, diagnosed with Constitutional mismatch repair deficiency (CMMR-D) syndrome was described within this extended cohort. CMMRD syndrome results in an increased predisposition to a range of cancers, most commonly brain and hematological tumours in early childhood. The aims of this thesis were: (i) to determine the rate of extra-colonic cancers in the cohort of Lynch syndrome families in our colorectal cancer registry, (ii) to determine if MLH1 c.1528C>T is a founder mutation, and (iii) to focus on the CMMR-D syndrome as a branch of Lynch syndrome and to potentially use the hypermutability-status in CMMR-D to understand the diverse carcinogenesis in Lynch syndrome. Methods: The registry consisting of Lynch syndrome families was interrogated and analysed to address the aim (i). Haplotype analysis was performed using microsatellite markers around the MHL1 c.1528C>T mutation to determine founder effect for aim (ii). For aim (iii) whole exome sequencing was also performed in a Lynch/ CMMR-D syndrome family in order to investigate the extent of hypermutability in CMMR-D syndrome, and to develop a working hypothesis for carcinogenesis in CMMR-D and Lynch syndromes. Results: From the analysis of the registry it was noted that 396 individuals carried a disease-causing mutation in either MLH1 or MSH2; females have a relatively later age of onset (for cancer) than males and MLH1 mutation carriers develop cancers relatively earlier in life than in individuals with MSH2 mutations. The most common extra-colonic cancers were endometrial and breast in females; in males small bowel cancer was most common, after CRC. The cohort study revealed a large founder effect with the MLH1 c.1528C>T mutation, with the most common inferred (disease-associated) haplotype found in 25 of the 30 subjects tested; the disease-associated haplotype was not present in controls. The mutation aging analysis traced the mutation to be ~225 years old. The WES investigation of the nuclear family within which the CMMR-D patient, including acquired and germline mutations in tissues from the child with CMMR-D, revealed a range of pathways including the extracellular matrix, WNT signaling, TGFβ and p53 as acquiring significant numbers of variants as a result of the MMR deficiency. Discussion and Conclusion: The results which are indicative of the need to improve the Lynch syndrome mutation testing and management for all patients, also suggests the need to develop surveillance programs for extra-colonic cancers, which will improve compliance and disease-free survival. WES investigation of the nuclear family containing a child with CMMR-D point to the potential involvement of a range of pathways associated with cancer development which may be indirectly invoked in the process of tumorigenesis by the wide range of variants acquired as a result of mismatch repair deficiency. It is likely that some of these processes are also involved in the emergence of extracolonic cancers in individuals affected with Lynch syndrome (i.e. heterozygous for mutations in MMR genes).